2019
DOI: 10.1016/j.rmed.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Revefenacin, a once-daily, lung-selective, long-acting muscarinic antagonist for nebulized therapy: Safety and tolerability results of a 52-week phase 3 trial in moderate to very severe chronic obstructive pulmonary disease

Abstract: A B S T R A C TBackground: Prior replicate 12-week phase 3 trials demonstrated that once-daily doses of revefenacin inhalation solution at 88 μg and 175 μg produced significant bronchodilation over 24 h post dose in patients with moderate to very severe chronic obstructive pulmonary disease (COPD). The objective was to characterize the safety profile of revefenacin 88 μg and 175 μg over 52 weeks of treatment. Methods: In this randomized, parallel-group, 52-week trial (NCT02518139), 1055 participants with moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…Revefenacin treatment was shown to improve FEV 1 and respiratory health outcomes in a 52-week study with results similar to tiotropium via HandiHaler ® [8]. Revefenacin was well tolerated for 52 weeks and has a safety profile that supports its long-term use in patients with COPD [9]. In addition, revefenacin was not associated with adverse cardiovascular events [10,11].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Revefenacin treatment was shown to improve FEV 1 and respiratory health outcomes in a 52-week study with results similar to tiotropium via HandiHaler ® [8]. Revefenacin was well tolerated for 52 weeks and has a safety profile that supports its long-term use in patients with COPD [9]. In addition, revefenacin was not associated with adverse cardiovascular events [10,11].…”
Section: Introductionmentioning
confidence: 84%
“…However, in patients with comorbid diabetes, it may be more appropriate to limit the use of ICS to the minority of patients with COPD who might benefit. There were no safety issues identified with the use of revefenacin in patients with cardiac risk factors [7,9]. In a preclinical study, revefenacin was shown to be a high-affinity competitive antagonist at human recombinant muscarinic acetylcholine receptors with kinetic functional selectivity for M 3 over M 2 muscarinic acetylcholine receptors [27].…”
Section: Discussionmentioning
confidence: 99%
“…11 Longterm safety of revefenacin in clinical trials was demonstrated in a 52 week, randomized, tiotropium-controlled, phase III safety and tolerability trial. 12 Revefenacin was well tolerated during the phase III trials and had a safety profile that supports its long-term use in patients with COPD. 11,12 Many patients with COPD require combination bronchodilator therapy for symptom management, and because more than 40% of patients in the phase III trials of revefenacin were taking concomitant LABA-containing therapy, we performed a prespecified subgroup analysis in this patient population to evaluate the efficacy and safety of revefenacin in combination with LABA-containing bronchodilators.…”
Section: Introductionmentioning
confidence: 89%
“…Inclusion and exclusion criteria for the three studies have been described previously. 11,12 For the 12-and 52-week studies, we enrolled patients aged at least 40 years with moderate to very severe COPD, a smoking history of at least 10 packyears, a postipratropium FEV 1 /forced vital capacity ratio <0.7, and a postipratropium FEV 1 <80% of predicted normal and >700 ml at screening. Patients with a substantially increased risk for cardiovascular events, such as myocardial infarction within the past 6 months, unstable or In the 12-week studies, up to 40% of patients were permitted concomitant use of LABA (LABA cap, controlled through stratification during randomization) with or without ICS.…”
Section: Patients and Treatmentsmentioning
confidence: 99%
“…There were no safety issues identified with the use of revefenacin in patients with cardiac risk factors [7,9]. In a preclinical study, revefenacin was shown to be a high-affinity competitive antagonist at human recombinant muscarinic acetylcholine receptors with kinetic functional selectivity for M 3 over M 2 muscarinic acetylcholine receptors [27].…”
Section: Tdi Respondersmentioning
confidence: 99%